Protective walls against effects of vapor cloud fast deflagration: CFD recommendations for design. Issue 1 (28th September 2017) - Vyazmina, Elena; Jallais, Simon; Beccantini, Alberto; Trélat, Sophie
Abstract : Protective walls are a well‐known and efficient way to mitigate overpressure effects of explosions. For detonation there are multiple published investigations concerning interactions of blast waves and walls, whereas for deflagration no well‐adapted and rigorous method has been reported in the literature. This article describes the validation of a new computational fluid dynamics (CFD) modeling approach for fast deflagrations. In a first step, the vapor cloud explosion involving a fast deflagration is substituted by an equivalent vessel burst problem. The purpose of this step is to avoid reactive flow computations. In a second step, CFD is used to model the pressure propagation from the equivalent (nonreactive) vessel burst problem. After verifying the equivalence of the fast deflagration and the vessel burst problem in the first step, the ability of two CFD codes FLACS and Europlexus is examined for situations with and without barriers. Parametric analysis by means of numerical simulations is performed to investigate the efficiency of finite barriers to mitigate blast waves. Another parametric study shows how the maximum overpressure value in the shade of the barrier depends on the magnitude of the incoming overpressure wave. On this basis, several recommendations are suggested for designing protective walls. © 2017 American Institute of Chemical Engineers Process Process Saf Prog 37:56–66, 2018